O dilema sobre a teoria da responsabilidade civil adotada pela lgpd no contexto de ineficiência do consentimento como base legal apta a tutela da autodeterminação informacional - CARDOSO, Luana Marron da Silva (2024)
This article aims to analyze which theory of civil liability was adopted by the Lei Geral de Proteção de Dados (LGPD): objective or subjective theory. The question is if the theory of liability adopted is adequate to resolve issues involving the adoption of the legal basis of consent, especially considering the poor effectiveness of this legal basis for promoting the informational self-determination of data subjects and the vulnerability of these subjects. The research has a theoretical-descriptive profile and a qualitative bias, which is proposed within a critical and reflective perspective. This article was deleveloped by the deductive method, the literature review procedure and the bibliographic research technique specialized in the subject. The article is divided in three items: the first presents and critically analyzes important conceptual definitions envisaged by LGPD, with emphasis on the concept of personal data and sensitive personal data, the definition of consent and the legal provision of the right to informational self-determination; the second item explains the problems involving the use of consent as a legal basis; and finally, the last item addresses the controversies involving the understanding of three authors regarding the theory of civil liability provided by LGPD. The research has concluded that the theory adopted was the subjective theory due to several provisions aimed at considering the fault of the data processing’s agent. However, the study suggests that the theory of objective liability is the most viable to protect the most vulnerable parties in the relationship, which are the personal data subjects.